Tren-tren Kultur Hidup Bergereja Pada Era Digital-Pandemi Covid-19 - Amos Sukamto (Sekolah Tinggi Teologi Berita Hidup, 2021)
AbstractThe hallmark of the Industrial Revolution 4.0 and Society 5.0 is that the culture of digitization plays a very important role in human life. This culture ushered humans into an era called digitized societies. Everything is digital. The Covid-19 pandemic has accelerated these changes, which of course also have an impact on the culture of church life. By using the survey method, it is found that several trends in church culture today: (1) The church suddenly became a digital church (online, virtual). (2) The presence of church congregations in online worship is still very diligent, especially the Boomers generation. There is a tendency for young people to be less diligent in worship. (3) Congregation participation in online worship is still very good, they are involved in the liturgical flow of worship and respond to the preaching of God's Word. (4) Even though the congregation is still loyal to its church, there is a tendency to become more liquid (liquid church members). They attend online services hosted by other churches. Of course, this culture will become a trend in the future that will color the culture of church life. (5) After the Covid-19 pandemic, the trend in the culture of the church congregation will choose the phygital church, and the onsite church is still a cultural trend that colors the life of the church congregation because Indonesian people are still very attached to the Gemeinschaft type of society. Ciri Revolusi Industri 4.0 dan Masyarakat 5.0 adalah kultur digitalisasi memainkan peran yang sangat penting dalam kehidupan umat manusia. Kultur ini menghantarkan manusia masuk pada sebuah era yang disebut digitized societies. Everything is digital. Pandemi Covid-19 mengakselerasi perubahan-perubahan tersebut yang tentunya berdampak juga pada kultur hidup bergereja. Dengan menggunakan metode survei didapatkan beberapa tren kultur hidup bergereja pada masa kini: (1) Gereja mendadak menjadi gereja digital (online, virtual). (2) Kehadiran jemaat gereja dalam ibadah online masih sangat baik khususnya generasi Boomers. Terdapat kecenderungan usia muda kurang rajin dalam beribadah. (3) Partisipasi jemaat dalam ibadah online masih sangat baik, mereka ikut terlibat alur liturgi ibadah dan memberikan respons pada pemberitaan Firman Tuhan. (4) Meskipun jemaat masih setia pada gerejanya namun ada kecenderungan menjadi lebih cair (liquid church member). Mereka menghadiri ibadah online yang diselenggarakan oleh gereja-gereja lain. Tentunya kultur ini akan menjadi tren ke depan yang akan mewarnai kultur hidup bergereja. (5) Pasca pandemi Covid-19 kecenderungan tren kultur jemaat gereja akan memilih phygital church, dan gereja onsite masih menjadi tren kultur yang mewarnai kehidupan jemaat gereja karena masyarakat Indonesia masih sangat lekat dengan tipe masyarakat Gemeinschaft.